Secondary erythrocytosis due to hypoxemia as prognosis in exacerbated chronic pulmonary diseases (2016)
Introduction: Even though exacerbations are the main cause of emergency consultation in patients suffering from lung diseases, erythrocyte parameters are not assessed in their prognosis. Thus, determining the implications of erythrocyte parameters might contribute to define the usefulness of phlebotomy or red blood cells transfusion in these patients.Objective: To establish a possible relationship between the different hematocrit levels with a 30-day prognosis in patients admitted with exacerbated chronic lung disease and hypoxemia.Materials and methods: A study based on a 30-day follow-up was conducted. Variables were described using an additional categorization by hematocrit levels and an adjustment in a multivariate model through logistic regression.Results: Follow-up was completed for 110 Patients. The frequency of anemia was 7.3% and of erythrocytosis, 14.5%. A significant association to the outcome using Anthonisen score (OR=10.45, 95%CI: 1.11-98.48, p=0.04), hypertension (OR=11.02, 95%CI: 1.32-91.75, p=0.026) and heart failure (OR=0.09, 95%CI: 0.01-0.82, p=0.032) was found.Conclusion: This research could not determine any relationship between erythrocyte parameters and prognosis of patients suffering from pulmonary diseases; nevertheless, extreme values of hematocrits tended to have adverse outcomes.